Putting Global Governance in Its Place - Rodrik, Dani (Published by Oxford University Press on behalf of the World Bank, 2021)
Greater interdependence is often taken to require more global governance, but the logic requires scrutiny. Cross-border spillovers do not always call for international rules. The canonical cases for global governance are based on two sets of circumstances: global commons and “beggar-thy-neighbor” (BTN) policies. The world economy is not a global commons (outside of climate change), and much of our current discussions deal with policies that are not true BTNs. Some of these are beggar-thyself policies; others may produce domestic benefits, addressing real market distortions or legitimate social objectives. The case for global governance in such policies, I will argue, is very weak, and possibly outweighed by the risk that global oversight or regulation would backfire. While these policy domains are certainly rife with failures, such failures arise not from weaknesses of global governance, but from failures of national governance and cannot be fixed through international agreements or multilateral cooperation. I advocate a mode of global governance that I call “democracy-enhancing global governance,” to be distinguished from “globalization-enhancing global governance.”